Impact of SLCO1B1 Genotype on Pediatric Simvastatin Acid Pharmacokinetics. (22nd February 2018) - Wagner, Jonathan B.; Abdel‐Rahman, Susan; Van Haandel, Leon; Gaedigk, Andrea; Gaedigk, Roger; Raghuveer, Geetha; Kauffman, Ralph; Leeder, J. Steven
Abstract: This study investigated the impact of allelic variation in SLCO1B1, a gene encoding for the liver‐specific solute carrier organic anion transporter family member 1B1 protein (SLCO1B1), on simvastatin and simvastatin acid (SVA) systemic exposure in children and adolescents. Participants (8–20 years old) with at least 1 variant SLCO1B1 c.521T>C allele (521TC, n = 15; 521CC, n = 2) and 2 wild‐type alleles (521TT, n = 15) completed a single oral dose pharmacokinetic study. At equivalent doses, SVA exposure was 6.3‐ and 2.5‐fold greater in 521CC and TC genotypes relative to 521TT (Cmax, 2.1 ± 0.2 vs 1.0 ± 0.5 vs 0.4 ± 0.3 ng/mL; P  < .0001; and AUC, 12.1 ± 0.3 vs 4.5 ± 2.5 vs 1.9 ± 1.8 ng·h/mL; P  < .0001). The impact of the SLCO1B1 c.521 genotype was more pronounced in children, although considerable interindividual variability in SVA exposure was observed within genotype groups. In addition, SVA systemic exposure was negligible in 25% of pediatric participants. Further investigation of the ontogeny and genetic variation of SVA formation and SLCO1B1‐mediated hepatic uptake is necessary to better understand the variability in SVA exposure in children and its clinical consequences.